The coordinated activities of collagen VI and XII in maintenance of tissue structure, function and repair: evidence for a physical interaction - Gregory, Carl A.; Ma, Jocelyn; Lomeli, Sebastian (Frontiers in Molecular Biosciences, 2024)
Collagen VI and collagen XII are structurally complex collagens of the extracellular matrix (ECM). Like all collagens, type VI and XII both possess triple-helical components that facilitate participation in the ECM network, but collagen VI and XII are distinct from the more abundant fibrillar collagens in that they also possess arrays of structurally globular modules with the capacity to propagate signaling to attached cells. Cell attachment to collagen VI and XII is known to regulate protective, proliferative or developmental processes through a variety of mechanisms, but a growing body of genetic and biochemical evidence suggests that at least some of these phenomena may be potentiated through mechanisms that require coordinated interaction between the two collagens. For example, genetic studies in humans have identified forms of myopathic Ehlers-Danlos syndrome with overlapping phenotypes that result from mutations in either collagen VI or XII, and biochemical and cell-based studies have identified accessory molecules that could form bridging interactions between the two collagens. However, the demonstration of a direct or ternary structural interaction between collagen VI or XII has not yet been reported. This Hypothesis and Theory review article examines the evidence that supports the existence of a functional complex between type VI and XII collagen in the ECM and discusses potential biological implications.